Finnougrisch-slawische Kontakte in der Vorgeschichte und Geschichte Russlands. Juhani Nuorluoto (ed.), The Slavicization of the Russian North: Mechanisms and chronology - Johanna Laakso (Department of European and Comparative Literature and Language Studies, Faculty of Philological and Cultural Studies, University of Vienna) (Finno-Ugrian Society (Suomalais-Ugrilainen Seura), Helsinki, 2006)
The abstract is available here: https://uscholar.univie.ac.at/o:299876 The abstract is available here: https://uscholar.univie.ac.at/o:299876 The abstract is available here: https://uscholar.univie.ac.at/o:299876